HNRNPH1‐related syndromic intellectual disability: Seven additional cases suggestive of a distinct syndromic neurodevelopmental syndrome. Issue 1 (15th May 2020) - Reichert, Sara C.; Li, Rachel; A. Turner, Scott; van Jaarsveld, Richard H.; Massink, Maarten P.G.; van den Boogaard, Marie‐José H.; del Toro, Mireia; Rodríguez‐Palmero, Agustí; Fourcade, Stéphane; Schlüter, Agatha; Planas‐Serra, Laura; Pujol, Aurora; et al.
Abstract: Pathogenic variants in HNRNPH1 were first reported in 2018. The reported individual, a 13 year old boy with a c.616C>T (p.R206W) variant in the HNRNPH1 gene, was noted to have overlapping symptoms with those observed in HNRNPH2‐ related X‐linked intellectual disability, Bain type (MRXSB), specifically intellectual disability and dysmorphic features. While HNRNPH1 variants were initially proposed to represent an autosomal cause of MRXSB, we report an additional seven cases which identify phenotypic differences from MRXSB. Patients with HNRNPH1 pathogenic variants diagnosed via WES were identified using clinical networks and GeneMatcher. Features unique to individuals with HNRNPH1 variants include distinctive dysmorphic facial features; an increased incidence of congenital anomalies including cranial and brain abnormalities, genitourinary malformations, and palate abnormalities; increased incidence of ophthalmologic abnormalities; and a decreased incidence of epilepsy and cardiac defects compared to those with MRXSB. This suggests that pathogenic variants in HNRNPH1 result in a related, but distinct syndromic cause of intellectual disability from MRXSB, which we refer to as HNRNPH1 ‐related syndromic intellectual disability. Abstract :